6 - Stratégie d'industrialisation et voie africaine du développement: by Florent Valère Adegbidi - Florent Valère Adegbidi, (Africa Development, 1994)
After reviewing the various strategies of industrialisation implemented in Third World countries with more or less success, this study focuses on the danger of the technical dependence which Africa is going through It underlines the fact that any serious industrial policy should first be based on controlling this variable as a strategic objective. It is important and necessary that Africa creates an alternative industrial development which will learn from what has made some small-scale African enterprises dynamic. Such an approach would among other things tackle the crucial problem of urban concentration.